STRATEGIES FOR ENHANCING SELF-DIRECTED LISTENING PROFICIENCY: INVESTIGATING EFL STUDENTS' AUTONOMOUS LEARNING PATHWAYS - Yunus, Reski Yusrini Islamiah; Sri Damayanti (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
This study delves into the efficacy of self-directed learning (SDL) strategies in improving listening comprehension skills among English as a Foreign Language (EFL) learners, a critical aspect of language acquisition that has seen limited exploration in current educational research. With the advent of technological advancements and the increasing demand for autonomous learning capabilities, this research focuses on identifying the autonomous learning strategies employed by EFL students and the challenges they face in enhancing their listening skills outside the conventional classroom setting. Utilizing a qualitative research methodology, data were collected through open-ended questions via Google Forms from the fourth-semester students of the English Study Program at Cokroaminoto Palopo University, selected through purposive sampling based on their engagement and interest in self-directed listening activities. The thematic analysis of the responses provided deep insights into the nuanced experiences of students, revealing a significant reliance on a variety of listening materials, including podcasts, movies, and digital platforms, which not only facilitated linguistic development but also fostered a profound sense of learner autonomy. The results highlight the crucial role of metacognitive awareness and the strategic application of listening comprehension strategies in boosting learners’ confidence and proficiency. Additionally, the study emphasizes the need for educational frameworks that support SDL practices with targeted instructional resources and approaches to effectively address listening comprehension barriers. This research underscores the importance of integrating SDL into language education to prepare learners for the global communication challenges of the 21st century, advocating for an educational model that emphasizes learner autonomy, metacognitive strategy training, and the utilization of multimodal learning resources.